VOLATILITY OF GOLD AND OIL PRICES ON THE INDONESIAN STOCK MARKET IN GEOPOLITICAL CRISIS - Hadi, Natanael Kristolife Ardana; Robiyanto, Robiyanto (Among Makarti, 2025)
Abstract : This study investigates the impact of oil and gold price volatility on stock market returns in Indonesia during periods of geopolitical instability, specifically the Russia-Ukraine conflict and the Israel-Hamas crisis. Utilizing secondary data, the research analyzes the daily closing prices of West Texas Intermediate (WTI) crude oil, Brent Crude Oil, gold, and the Jakarta Composite Index (JCI). The Generalized Autoregressive Conditional Heteroskedasticity (GARCH) (1,1) model is employed as the primary analytical framework. The findings reveal that oil and gold price volatility exerts a positive and unidirectional influence on Indonesian stock returns during the aforementioned geopolitical crises. This suggests that investors tend to seek safe-haven assets, such as gold, in times of economic uncertainty and geopolitical turmoil. The increased volatility in gold prices is indicative of heightened market instability, particularly during financial crises and geopolitical disruptions. These results corroborate the notion of gold serving as a reliable safe-haven asset during periods of economic and geopolitical uncertainty.Abstrak : Penelitian ini menyelidiki dampak volatilitas harga minyak dan emas terhadap imbal hasil pasar saham di Indonesia selama periode ketidakstabilan geopolitik, khususnya konflik Rusia-Ukraina dan krisis Israel-Hamas. Dengan memanfaatkan data sekunder, penelitian ini menganalisis harga penutupan harian minyak mentah West Texas Intermediate (WTI), Brent Crude Oil, emas, dan Indeks Harga Saham Gabungan (IHSG). Model Generalized Autoregressive Conditional Heteroskedasticity (GARCH) (1,1) digunakan sebagai kerangka analisis utama. Temuan penelitian ini mengungkapkan bahwa volatilitas harga minyak dan emas memberikan pengaruh positif dan searah terhadap imbal hasil saham Indonesia selama krisis geopolitik tersebut. Hal ini menunjukkan bahwa investor cenderung mencari aset safe haven, seperti emas, di saat ketidakpastian ekonomi dan gejolak geopolitik. Meningkatnya volatilitas harga emas merupakan indikasi meningkatnya ketidakstabilan pasar, terutama selama krisis keuangan dan gangguan geopolitik. Hasil ini menguatkan gagasan bahwa emas berfungsi sebagai aset safe haven yang andal selama periode ketidakpastian ekonomi dan geopolitik.